Design of Augmented Reality-Based Learning Media Integrating Islamic Values for Teaching Atomic Structure - Wiliyanti, Vandan; Yuberti, Yuberti (Jurnal Pembelajaran Fisika, 2024)
This research examines the creation of augmented reality-based educational media for physics that incorporates Islamic principles, primarily aimed at teaching atomic structure. The study sought to ascertain the appropriateness of augmented reality (AR) media in improving students' comprehension of atomic structure while simultaneously imparting Islamic precepts. This study utilizes the Research and Development (R&D) methodology, consistent with the ADDIE paradigm (analysis, design, development, implementation, and evaluation). Data was acquired by administering a questionnaire to specialists in media, materials, and Islamic religion to assess the viability of the learning medium. The questionnaire addressed three primary aspects: media design, content relevance, and the incorporation of Islamic principles. This research employs descriptive quantitative and qualitative analysis approaches. The study concentrated on evaluating the development of AR media, its practicality, and the congruence of the content with Islamic beliefs. The findings of this study demonstrate that the AR-based learning medium is exceptionally appropriate for physics instruction. The media validation achieved a score of 86%, the material validation received 88%, and the integration of Islamic principles attained 85%, indicating the medium's efficacy and suitability. This augmented reality educational medium facilitates the cognitive and ethical maturation of students, underscoring its advantages for attaining both scholarly superiority and moral advancement.Keywords: Augmented reality, Islamic values, atomic structure, learning media, ADDIE modelDOI: http://dx.doi.org/10.23960/jpf.v12.n2.202406